Sudden cessation of fluoxetine before alcohol drinking reinstatement alters microglial morphology and TLR4/inflammatory neuroadaptation in the rat brain - Aranda, Jesús; Fernández-Arjona, María del Mar; Alén, Francisco; Rivera-González, Patricia; Rubio-Lamia, Leticia Olga; Smith-Fernández, Inés María (Springer, 2021)
Preclinical studies on the efects of abrupt cessation of selective serotonin reuptake inhibitors (SSRIs), a medication often prescribed in alcohol use disorder (AUD) patients with depression, results in alcohol consumption escalation after resuming drinking. However, a potential neuroinfammatory component on this escalation remains unexplored despite the immunomodulatory role of serotonin. Here, we utilized a rat model of 14-daily administration of the SSRI fuoxetine (10 mg/kg/day) along alcohol self-administration deprivation to study the efects of fuoxetine cessation on neuroinfammation after resuming alcohol drinking. Microglial morphology and infammatory gene expression were analyzed in prelimbic cortex, striatum, basolateral amygdala and dorsal hippocampus. Results indicated that alcohol drinking reinstatement increased microglial IBA1 immunoreactivity and altered morphometric features of activated microglia (fractal dimension, lacunarity, density, roughness, and cell area, perimeter and circularity). Despite alcohol reinstatement, fuoxetine cessation modifed microglial morphology in a brain region-specifc manner, resulting in hyper-ramifed (spatial complexity of branching), reactive (lower heterogeneity and circularity)-like microglia. We also found that microglial cell area correlated with changes in mRNA expression of chemokines (Cx3cl1/fractalkine, Cxcl12/SDF1α, Ccl2/MCP1), cytokines (IL1β, IL6, IL10) and the innate immune toll-like receptor 4 (TLR4) in dorsal hippocampus. Specifcally, TLR4 correlated with microglial spatial complexity assessed by fractal dimension in striatum, suggesting a role in process branching. (...)
Keywords: Alcohol; Antidepressant; Hippocampus; Infammation; Microglia; Fractal dimension